Vibrational Spectroscopic Investigation Of Free And Coordinated 5-Aminoquinoline: The IR, Raman And DFT Studies - Özel, Ayşen E.; Çelik, Sefa; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2009)
Combined experimental and computational vibrational spectra of 5-aminoquinoline (5-AQ) and its zinc chloride complex {Zn(5-AQ)(2)Cl-2}, together with the computational results of 5-AQ interacting with H2O through the ring nitrogen {5-AQ center dot H2O} have been reported. The geometry of the free 5-AQ were optimized using DFT method at B3LYP/6-31G(d,p) and 6-31++G(d,p) levels of theory. Coordinated 5-AQ molecules: {5-AQ center dot H2O} and {Zn(5-AQ)(2)Cl-2} were optimized using DFT/B3LYP/6-31G(d,p) level of theory. Harmonic and anharmonic vibrational frequencies and infrared intensities were calculated at the same level of theory. The fundamental vibrational modes were characterised depending on their total energy distribution (TED%). Coordination effects on 5-AQ vibrational frequencies were investigated. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ab Initio Calculations; DFT; Aminoquinolin; IR and Raman Spectra; Vibrational Frequencies; Zn Halide Complex; Density-Functional Theory; Ft-Raman; Complexes; Molecule; Spectra; Titreşim Frekansları; Zn Halojenür Kompleksi; Yoğunluk Fonksiyonel Teorisi; Kompleksler; Molekül; Spektrumlar